What is the Economic Action? - Vadim Radaev (Journal of Economic Sociology, 2010)
This is a methodological work. One of the main terms is thoroughly discussed here about which we do not think but have constant latent difficulties. The author gives the definition of economics, discloses the constitution elements of economic action, compares economically conditioned and economically oriented actions, and formulates the peculiarities of economic-sociological approach to this subject.